(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
A novel DNA biosensing platform was designed by the functionalization of iron oxide (Fe3O4) with the carboxylic group via capping agent, mercaptopropionic acid (MPA) and conjugated with nanocellulose crystalline (NCC) surface modified with surfactant cetyltrimethylammonium bromide (CTAB) to assist in the DNA sensing capability. The product of nanocomposites compound was drop-casted on screen printed carbon electrode (SPCE). Characterization by field emission scanning electron microscope (FESEM) and energy dispersive X-Ray (EDX) spectroscopy showing that carboxyl functionalized iron oxide (COOH-Fe3O4) can be hybridized with NCC-CTA+ via electrostatic interaction.